Abuse, invalidation, and lack of early warmth show distinct relationships with self‐criticism, self‐compassion, and fear of self‐compassion in personality disorder. (27th February 2019) - Naismith, Iona; Zarate Guerrero, Santiago; Feigenbaum, Janet
Abstract: Background: Cultivating self‐compassion is increasingly recognized as a powerful method to regulate hyperactive threat processes such as shame and self‐criticism, but fear of self‐compassion (FSC) can inhibit this. These difficulties are underexplored in personality disorder (PD) despite their prevalence. Furthermore, little evidence exists regarding how these factors relate to adverse childhood experiences (ACEs) and attachment. Method: Fifty‐three participants with a diagnosis of PD completed measures including childhood abuse/neglect, invalidation, early warmth, self‐compassion, shame, self‐criticism, FSC, and anxious/avoidant attachment. Results: Self‐compassion was predicted uniquely by low early warmth; self‐inadequacy by invalidation and abuse; and FSC by multiple ACEs. FSC and self‐compassion were significantly correlated with self‐criticism and shame, but not with one another. Conclusions: Low self‐compassion and high FSC appear to be distinct problems, substantiating physiological models proposing distinct threat and soothing systems. Results are consistent with theories positing that low self‐compassion has distinct origins to shame, self‐criticism, and FSC.